A Novel Fuzzy Theory-Based Differential Protection Scheme for Transmission Lines - Abasi, Mahyar; Farsani, Ahmad Torabi; Rohani, Arash; Beigzadeh, Arsalan (International Journal of Integrated Engineering, 2020)
Abstract- Ever-increasing consumption of electrical energy has forced extension of power systems to wider regions, which will augment concerns about the stability and reliability of power systems. Therefore, a special attention has been given to protection systems and protection relays to improve these concerns. By appropriate design of protection systems and proper function of protection relays, it is possible to reduce the adverse effects of undesirable faults. A fuzzy logic-based algorithm is presented to improve differential relay performance. The algorithm is employed for protection of short transmission lines against internal faults with/without resistance. By using fuzzy logic and selecting the best stability characteristics, the possibility of malfunction of protection relays will be negligible. In this algorithm, sensitivity, reliability and speed of the relay performance are preserved at suitable levels. The proposed algorithm is also very beneficial for external faults accompanied with the saturation of current transformers (CTs). The purpose of this study is to present an algorithm based on the fuzzy logic, which can decide on the slope of stability characteristics of a differential relay in the best way during various conditions. The performance of the presented algorithm is analyzed in PSCAD/EMTDC program and compared to conventional methods.